2016
DOI: 10.14687/jhs.v13i3.4104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of demographic features to middle school students’ attitude towards FeTeMM (STEM)

Abstract: In this research, which is done in order to determine the demographical features on middle school students' 6 th , 7 th and 8 th grades towards FeTeMM (STEM), scanning design is used. It is performed with 581 middle school students, and data are collected through Middle School Students' point of view to Stem (S-Stem) scale. The research is implemented during 2015-2016 spring period. For statistical evaluation of gathered data, independent t-test and one direction variance analysis (anova), one direction varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
23
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 9 publications
4
23
0
3
Order By: Relevance
“…In the study, opinions of teachers about STEM education were examined and no significant relation was identified in terms of gender variable. This result is also in accordance with some studies (Karakaya and Avgın, 2016;Yenilmez and Balbağ, 2016). Furthermore, no significance was observed between the views of teachers with science, mathematics and information technologies and their branches.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…In the study, opinions of teachers about STEM education were examined and no significant relation was identified in terms of gender variable. This result is also in accordance with some studies (Karakaya and Avgın, 2016;Yenilmez and Balbağ, 2016). Furthermore, no significance was observed between the views of teachers with science, mathematics and information technologies and their branches.…”
Section: Conclusion and Discussionsupporting
confidence: 93%
“…Yürütülen pek çok çalışmada STEM eğitimine ilişkin uygulamaların öğrencilerin bu alanlara ilişkin tutumlarında pozitif yönde bir etki sağladığını desteklemektedir (Aydın, Saka ve Guzey, 2017;Baran vd., 2016;Chonkaew, Sukhummek ve Faikhamta, 2016;Guzey vd., 2016;Gülhan ve Şahin, 2016;Karakaya ve Avgın, 2016;Karahan vd., 2015;Yamak vd., 2014;Toma ve Greca, 2018;Yerdelen, Kahraman ve Taş, 2016). STEM'e yönelik tutumların ve bu tutumların STEM kariyer alanları ile ilişkisinin araştırıldığı bir çalışmada; STEM'e yönelik olumlu tutuma sahip öğrencilerin bu alanlarda kariyer yapmaya daha eğilimli olduklarını göstermiştir (Yerdelen vd., 2016).…”
Section: Bulgularunclassified
“…These results suggest that there is a need for new strategies to increase women's interest in engineering and technology, and the need to find ways of maintaining student interest in STEM as they age. However, Karakaya and Avgın (2016) concluded that attitudes of the female students towards STEM are higher than those of males. In a similar vein, in their study with 813 secondary school students, Christensen, and Knezek (2017) concluded that male students want to maintain a career in STEM and also show more interest in STEM fields.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, basic mathematical skills of females are significantly higher than those of males. When literature studies are examined, it is noted that there are STEM studies mostly on gender differences related to attitudes (Badur, 2018;Christensen & Knezek, 2017;Karakaya & Avgın, 2016;Unfried, Faber & Wiebe, 2014). For instance, Unfried, Faber and Wiebe (2014) conducted a study to measure the attitudes of 7032 secondary and 1324 high school students towards STEM subjects and their interest in STEM careers.…”
Section: Discussionmentioning
confidence: 99%